Stock Plant Production and Management Basics for Small Greenhouse Businesses - James L. Gibson; Christopher B. Cerveny (EDIS)
Vegetative propagation is an important component of ornamental plant production, because noteworthy characteristics such as flower color or leaf variegation remain true to type from the stock plant, unlike the varied results achieved through seedling propagation. Therefore, maintaining good stock or “mother plants” is critical for success down the road. Poor stock plant management leads to poor quality cuttings. This document contains information that provides some basic guidelines for successful stock plant management and stem cutting production. This document is ENH1021, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date December 7, 2005.